2023
DOI: 10.1088/2058-8585/acc4d7
|View full text |Cite
|
Sign up to set email alerts
|

Paper-based wearable ultra-sensitive strain sensors for fitness monitoring

Abstract: Emerging technologies that exhibit features of biodegradability and eco-friendliness are potential game changers. Paper is a cost-effective and easily available material that has proved itself a promising candidate for the manufacturing of strain sensors due to its easy integration into flexible electronics. In this work, an ultra-sensitive and highly stable strain sensor is presented. The modified interdigital capacitor (MIDC) structure is fabricated on a simple printing paper whereas copper tape is used as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…So, this is the whole principle that explains why capacitance changes upon bending. [18] The pictorial explanation of the working mechanism can be found in Figure S2, Supporting Information.…”
Section: Expermental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…So, this is the whole principle that explains why capacitance changes upon bending. [18] The pictorial explanation of the working mechanism can be found in Figure S2, Supporting Information.…”
Section: Expermental Sectionmentioning
confidence: 99%
“…In the last decade, flexible materials have been widely investigated for manufacturing flexible strain sensors. The flexible strain sensors are prepared extensively for use in several applications like fatigue monitoring, [11] human-machine interface, [12] electronic skin, [13] and many others.Enormous studies reported on flexible strain sensors, which include flexible substrates like polydimethylsiloxane, [14] thermoplastic polyurethane, [15] Ecoflex, [16] silicon rubber, [17] paper, [18,19] and lot more. Continuous wearing of these materials does not prove themselves a promising selection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the preparation of the strain sensors mentioned above is simple and flexible, their sensitivity in detecting human joint motion is low and they cannot respond quickly to external stimuli. Therefore, optimizing sensor performance to achieve accurate hand motion monitoring while ensuring a simple and flexible preparation process is the main challenge faced by current researchers [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Flexible electronics and wearable electronic devices have demonstrated a considerable application potential for flexible sensing technology [ 6 ], which has also received extensive research. Flexible sensors with resistive, capacitive, inductive, triboelectric, and other sensing techniques were used to measure mechanical amounts [ [6] , [7] , [8] , [9] , [10] , [11] , [12] ]. Due to its low price, the lightweight, easily accessible cellulose-based paper has gained popularity recently.…”
Section: Introductionmentioning
confidence: 99%